Silat pangean: maintaining togetherness and respect in the Panggak Adat procession in Kota Baru Village, Riau Province - Musrin, Musrin; Erawati , Yahyar; Idawati , Idawati; Syefriani , Syefriani (Gelar: Jurnal Seni Budaya, 2024)
Silat Pangean is an art form that features martial arts movements. Silat Pangean has an important role in various traditional ceremonies, especially in Kota Baru Village, Riau Province. Silat Pangean is inseparable in the procession of Panggak Adat where Silat Pangean becomes part of the custom in Kota Baru Village which becomes one unit.  Silat Pangean is performed early in the Panggak Adat procession which aims to welcome the arrival of the groom as a form of friendship between the two parties. The function of the fighter after the silat performance is over is to guard the bride and groom while the Panggak Adat is taking place. This research aims to find out how the series of Silat Pangean performances in the procession of traditional wedding Panggak in Kota Baru Village, Riau Province. The method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that Pangean Silat in Kota Baru Village is not only a martial art, but also an entertainment silat that has an important role in the Panggak Adat procession in Kota Baru Village. The form of Silat Pangean performance is seen from several elements such as clothing, musical accompaniment, audience, stage and players. This research is expected to contribute to the development of cultural studies and local traditions, as well as increase awareness of the importance of preserving cultural heritage in Indonesia, especially in Riau Province.